Changing Paradigms in Drug Discovery: Scientific Business Intelligence™ and Workflow Solutions - Varma-O'Brien, Shikha; Brown, Frank K.; LeBeau, Andrew; Brown, Robert D. (Current Computer - Aided Drug Design, 2008)
Workflow solutions driven by data pipelining are increasingly becoming popular for accessing, aggregating and analyzing disparate data to make informed and intelligent decisions. Uses of workflow technologies which facilitate business intelligence (BI) improve productivity, decision making and research efficiency. In order to provide BI in a scientific or clinical based organization, it is imperative that the application or workflow technology must be compatible with multiple data types and formats, be able to analyze the data and make it available throughout the organization. We term this as Scientific Business Intelligence (SBI) and discuss how modeling, simulations and informatics software, integrated with open and standards-based scientific operating platform (SOP), can deliver scientifically-relevant BI solutions. We illustrate SBI with several examples encompassing all levels of users within an organization.
Keywords: Pipeline Pilot™